Comparison of Bankruptcy Application Procedures Between Regional-Owned Enterprises (BUMD) and State-Owned Enterprises (BUMN) - M. Adi Putra; Zainal Arifin Hosein (Mahkamah : Jurnal Riset Ilmu Hukum, 2025)
This study aims to compare the bankruptcy application procedures between State-Owned Enterprises (BUMN) and Regional-Owned Enterprises (BUMD). Bankruptcy is a condition that significantly impacts economic stability, both nationally and regionally. In this case, both types of enterprises are regulated by different regulations but with similar underlying principles. Therefore, this research examines the differences and similarities in bankruptcy procedures for BUMN and BUMD, as well as the authority each possesses in the bankruptcy application process. Additionally, this study highlights the importance of harmonizing regulations governing bankruptcy procedures to ensure the coherence of the prevailing legal system. The research method used is normative legal research with a legislative approach and a conceptual approach. This research reveals that although there are similarities in objectives, significant procedural differences require adjustments to create uniformity and legal certainty in resolving bankruptcy issues for both types of enterprises.